Efektivitas Skor Wells dengan Pemeriksaan D-Dimer, Prothrombin Time, Activated Partial Thromboplastin Time dan Fibrinogen Terhadap Deteksi Dini Deep Vein Trhombosis di Ruang ICU RSPAD Gatot Soebroto - Rukmana, Aip; Sofiani, Yani; Agung, Rizki Nugraha (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2023)
Deep vein thrombosis (DVT) is a clinical disorder that occurs in the vein. The purpose of this study is to identify the effectiveness of the Wells score with D-Dimer, PT, APTT, and fibrinogen examinations for DVT early detection. cross-sectional research design to assess the validity of Wels scores and D-Dimer, PT, APTT, and Fibrinogen's examinations on DVT early detection. 70 respondents were chosen by the purposive sampling technique. In the results of sensitivity analysis using the True Positives/(True Positives + True Negatives) formula, the percentage of D-Dimer's sensitivity was obtained on the Wells score of 85.4%, PT on the Wells score percentage of 81.3%, Aptt against the Wells percentage score of 83.3%, and fibrinogen against the Wells scores with a percentage of 64.6%. It can be concluded that all variables have sufficient sensitivity values in determining DVT events by using Wells scores, but the most sensitive D-Dimer variable is D-Dimer in detecting the risk of DVT events. Researchers recommend that the results of this research be utilized as a reference in the development of instruments for the application of DVT early detection.